Adsorption thermodynamic and kinetic studies of Cr(VI) by chitosan flake modified with citric acid via crosslinking with glutaraldehyde - Yêu Ly, Ho Thi; Tong, Nguyen Xuan; Tan, Le Van (Vietnam Journal of Chemistry, 2016)
In this study, the sorption of Cr(VI) from aqueous solution onto the cross-linked chitosan grafting with citric acid (C-Gch) was investigated in a bath system. The optimum conditions for the adsorption were found to be pH 1 and 720 min of contact time. The maximum adsorption capacity of Cr(VI) at pH 1 was found to be 32 mg Cr(VI) /g C-Gch after 720 min of contact time.  Adsorption kinetic data were tested using pseudo-first order and pseudo-second order. The obtained results confirmed that the adsorption process of Cr(VI) followed the pseudo-second kinetic model. It was shown that the adsorption process is presumably a chemisorption. Thermodynamic parameters including changes in the standard free energy (∆G), enthalpy (∆H) and entropy (∆S) were also calculated. Keywords. Cr(VI), modified chitosan, citric acid, adsorption thermodynamic